Mechanical Thrombectomy in Patients with Acute Ischemic Stroke on Anticoagulation Therapy - Černík, David; Šaňák, Daniel; Divišová, Petra; Köcher, Martin; Cihlář, Filip; Zapletalová, Jana; Veverka, Tomáš; Prcúchová, Andrea; Ospalík, Dušan; Černá, Marie; Janoušová, Petra; Král, Michal; et al. (Cardiovascular and interventional radiology, 2018)
INTRODUCTION/PURPOSE: Mechanical thrombectomy (MT) for acute ischemic stroke (IS) can be performed also in patients on anticoagulation therapy (AT); however, sufficient and reliable data about safety and efficacy of MT are still missing. Thus, we aimed to compare these parameters between patients treated on AT and without AT. MATERIALS AND METHODS: All consecutive IS patients treated with MT using stent retrievers were included in the retrospective analysis. Neurological deficit was scored using National Institutes of Health Stroke Scale (NIHSS) and 90-day clinical outcome using modified Rankin scale with a score 0-2 for good outcome. Recanalization was rated using Thrombolysis in Cerebral Infarction (TICI) scale. Symptomatic intracerebral hemorrhage (SICH) was assessed according to the SITS-MOST criteria. RESULTS: Out of 703 patients treated with MT, 88 (12.5%) patients (46% males, mean age 75.5 ± 11.8 years) were on AT with an admission median NIHSS of 17 points. Recanalization (TICI 2b-3) was achieved in 80% and complete (TICI 3) in 65% of patients on AT and in 80 and 65% of patients without AT (p-1.000). SICH after MT was detected in 9% of AT and 5% of non-AT patients (p-0.136). Good outcome was present in 36% of AT patients (p-0.03). AT patients with poor outcome had more frequently atrial fibrillation (93%, p-0.005), higher admission NIHSS (17, p-0.004) and higher rate of SICH (14.5%, p-0.047). CONCLUSION: MT seems to be safe also in patients on AT. Poor outcome may be related to higher admission NIHSS, higher rate of SICH and presence of atrial fibrillation.
Keywords: Thrombectomy; Aged; Treatment Outcome; Retrospective Studies; senioři; trombektomie; Brain Ischemia; lidé; Stroke; ischemie mozku; Anticoagulants; Female; výsledek terapie; Male; ženské pohlaví; Humans; mužské pohlaví; cévní mozková příhoda; antikoagulancia; retrospektivní studie